A strategic framework for sustainable and responsible artisanal and small-scale gold and diamond mining in Ghana - Boaduo, Boaduo (My University, 2022)
Artisanal and small-scale mining (ASM) is an important economic activity in Ghana and a significant source of livelihood for many Ghanaian communities. The subsector has a mining value chain that has the potential to generate substantive mineral revenue in addition to employment. In the past, it has produced more gold than any single large-scale mining company in Ghana. ASM offers more employment and entrepreneurship opportunities than all the large-scale mines in Ghana combined. Despite these benefits, the sub-sector is inundated by negative realities. It has a negative image, it is largely illegal, perceived as unorganized and it is damaging to the environment. Although the government has made several efforts to reform ASM, Ghana still has much to do to ensure that the sub-sector can contribute more to the economy and citizens’ well-being. ASM is not well defined or understood, mining legislation does not reflect its current state (i.e. the more modern or semi-mechanized forms of mining), and mineral rights allocation systems lack transparency and appropriateness. In addition to this, the ASM value chain is weak compared to formal or large-scale mining. There has been little to no effort to develop or customize it so that it meets the needs of the sub-sector. Despite the current state, communities have a positive outlook and high hopes for the sub-sector. They believe that it has great potential and it can catalyse economic growth and development if it is manage correctly. This research develops a strategy called the PASE framework to help Ghana in working towards Professional, Accountable, Sustainable and Economic ASM. This strategy is driven by the vision of building a sustainable ASM sub-sector that uplifts communities and creates diverse economic opportunities. More importantly, it is informed by actual case study observations of small-scale mining operations in Ghana. The PASE framework is founded on 6 pillars, which address the key areas that need to be improved to move the Ghanaian ASM sub-sector forward. The framework is accompanied by an implementation plan (a roadmap to change) to help Ghana work towards the identified vision. The Ghanaian government is encouraged to consider the PASE framework and its implementation plan (through the Minerals Commission) in developing and empowering ASM for the benefit of Ghana’s economic growth and development.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Engineering and the Built Environment, School of Mining Engineering, University of the Witwatersrand, Johannesburg, 2022